Sex, Gender Identity, and Perceived Employability Among Spanish Employed and Unemployed Youngsters - Cifre, Eva; Vera, María; Sánchez-Cardona, Israel; de Cuyper, Nele (Frontiers in Psychology, 2018)
Young people find it difficult to access to the labor market, particularly in countries like Spain with a dramatically high rate of unemployment. A further problem is that this labor market is not gender-neutral. This has been demonstrated repeatedly in the literature, with women typically being at a disadvantage. This highlights the need to study issues related to employability from a gender perspective, beyond including sex as a mere control variable. This analysis is relevant given the gender biases in organizations and in society in general that hinder the advancement of gender equality in organizations. Accordingly, our aim is to study both sex (male vs female) and four profiles of gender identity based on dimensions of masculinity and femininity (i.e., feminine, masculine, undifferentiated and androgynous) in relation to perceived employability in an exploratory way in two samples of employed (N = 181) and unemployed (N = 246) Spanish youngsters (i.e., below 30). The results show different patterns for employed and unemployed youngsters regarding sex, gender identity and their interaction in relation to perceptions of being employable. Concerning sex, women seem more confident about their employment chances when unemployed. In contrast, men feel more confident about their employment chances within their organization than women when employed. Concerning gender identity, the androgynous gender profile in the employed sample (in both men and women) scored highest on perceived employability. Results of the sex-gender identity interaction show that being feminine associates with the highest level of perceived employability for an unemployed man and the lowest for an unemployed woman. Moreover, both unemployed men and women androgynous score the highest in perceiving employability (except feminine men). Our findings highlight that sex and gender identity do play a role in shaping employability perceptions of young men and women in different labor contexts (employment, unemployment). This reinforces the need of changes against discrimination at work and in job search from a feminist approach to arrive at a more equal society.